What does the Visual Image of a Teacher Have to do with the Prestige of the Teaching Profession? Some Research Experience on this Issue in Latvia - Kestere, Iveta; Kalke, Baiba; Berzins, Edgars (Journal of Education Culture and Society, 2025)
Aim. Our study explores how 14-15-year-olds in Latvia perceive the visual image of the teacher, highlighting contribution of visual communication to the prestige of the teaching profession. Our research poses two questions: (RQ1) Which indicators of occupational prestige are attributable to teacher’s visual image? (RQ2) How do pupils evaluate a teacher’s image based on these indicators, and what does this reveal about their expectations for visual communication with teachers?Methods. We conducted a qualitative study analysing the responses of 290 Latvian adolescents aged 14-15 to the question, “What does a typical teacher look like?” The analysis focused on four components related to the visual image of a teacher that reflect indicators of occupational prestige: gender, age, physical appearance, verbal communication (e.g., tone of voice), and non-verbal communication.Results. Pupils generally viewed teaching as a female-dominated profession, associating women teachers with kindness and care, and men with greater strictness. Age stereotypes were strong: teachers were often seen as “old,” with older staff described as strict, tired, or outdated, while younger teachers were valued for their energy, friendliness, and approachability. Pupils paid close attention to teachers’ communication styles, appreciating smiling, joking, and calmness, but criticising shouting, anger, and visible fatigue; they respected both cheerfulness and professional seriousness. In terms of appearance, neatness and modesty were preferred, and female teachers expected to be well-groomed but not sexualized.Conclusions. Pupils' responses highlight areas where visual communication can be improved: the findings indicate that respondents expect teachers to appear at least morally – if not physically – youthful, maintain a neat and discreet appearance, communicate in a cheerful manner, and avoid raising their voice to a shout.Originality. Although extensive research has explored both the image of teacher and the prestige of the teaching profession, the relationship between these two phenomena has received only limited attention. Our study reveals that a teacher’s professional prestige contains indicators influenced by the teachers themselves: specifically, our findings highlight elements of visual communication that educators can critically assess to enhance the prestige of their profession.